2016
DOI: 10.1158/1078-0432.ccr-15-2225
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Apitolisib (GDC-0980), Dual Phosphatidylinositol-3-Kinase and Mammalian Target of Rapamycin Kinase Inhibitor, in Patients with Advanced Solid Tumors

Abstract: Purpose This first-in-human phase I trial assessed the safety, tolerability, and preliminary anti-tumor activity of apitolisib (GDC-0980), a dual inhibitor of class I phosphatidylinositol-3-(PI3K) and mammalian target of rapamycin (mTOR) kinases. Experimental Design Once-daily (QD) oral apitolisib was administered to patients with solid tumors for days 1-21 or 1-28 of 28-day cycles. Pharmacokinetic and pharmacodynamic parameters were assessed. Results Overall, 120 patients were treated at doses between 2-7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 45 publications
3
68
0
Order By: Relevance
“…The safety profile observed in patients receiving LY3023414 for prolonged period of time was similar as for the overall patient population supporting the longterm tolerability of LY3023414 at the RP2D. Upper gastrointestinal toxicity and fatigue has been previously reported as a common AE for other PI3K/mTOR dual inhibitors with a dosedependent safety profile (17). Potentially due to LY3023414's short half-life with intermittent target inhibition, rash and hyperglycemia were infrequently observed, which contrasts with the toxicity profiles of other PI3K/mTOR inhibitors that commonly report higher rates for these adverse events.…”
Section: Discussionsupporting
confidence: 64%
“…The safety profile observed in patients receiving LY3023414 for prolonged period of time was similar as for the overall patient population supporting the longterm tolerability of LY3023414 at the RP2D. Upper gastrointestinal toxicity and fatigue has been previously reported as a common AE for other PI3K/mTOR dual inhibitors with a dosedependent safety profile (17). Potentially due to LY3023414's short half-life with intermittent target inhibition, rash and hyperglycemia were infrequently observed, which contrasts with the toxicity profiles of other PI3K/mTOR inhibitors that commonly report higher rates for these adverse events.…”
Section: Discussionsupporting
confidence: 64%
“…For example, inhibition of AKT signalling combined with inhibi tion of mTOR signalling, using combinations of AKT and mTOR inhibitors or dual PI3K-AKT and mTOR inhibitors, might be of value in promoting autophagy in OA. Novel monospecific and dual inhibitors of AKT, PI3K, mTORC1 and mTORC2 have been tested, or are currently being tested, in clinical trials for the treat ment of breast and other cancers [209][210][211][212][213][214][215][216][217] . Dual PI3K and mTOR inhibitors, and dual mTORC1 and mTORC2 inhibitors, had similar safety and tolerability profiles within each class of compound as well as to allosteric mTORC inhibitors in earlyphase clinical trials in this setting.…”
Section: Beclin-1 Complexmentioning
confidence: 99%
“…Dual PI3K and mTOR inhibitors, and dual mTORC1 and mTORC2 inhibitors, had similar safety and tolerability profiles within each class of compound as well as to allosteric mTORC inhibitors in earlyphase clinical trials in this setting. The main safety concerns associated with these multispecific agents were dermatological, hyper glycaemic and inflammatory toxicities, which were dependent on dose, the stage of disease progression and previous treatment regimens [210][211][212][213][214][215][216][217] . Although transami nase levels, an indicator of liver damage, were increased in trials of one dual mTORC1-mTORC2 inhibitor (no longer being developed) 210,212 , this finding has not been replicated with other compounds 211,217 .…”
Section: Beclin-1 Complexmentioning
confidence: 99%
“…gov NCT01655225). A phase I study evaluating safety and tolerability of apitolisib, a potent small molecule inhibit of PI3K and mTOR, reported a partial response in 2 out of 26 MPM patients (115). Recently, in vitro studies demonstrated that targeting MET and PI3Ks provides synergistic inhibition of MPM cell proliferation and migration, induction of apoptosis, and reduction in growth of an MPM patient derived xenograft mouse model (116), which provides a rationale for combinatorial therapy.…”
Section: Pi3k/akt/mtor Pathway Inhibitorsmentioning
confidence: 99%